A meta‐analysis examined the effect of oxidised regenerated cellulose/collagen dressing on the management of chronic skin wounds. Issue 5 (8th December 2022) - Chen, Yang; Du, Pan; Lv, Guozhong
Abstract: To assess the impact of oxidised regenerated cellulose/collagen dressing on the management of chronic skin wounds, we conducted a meta‐analysis. A thorough review of the literature up to September 2022 revealed that 1521 participants had chronic skin wounds at the start of the investigations; 763 of them used oxidised regenerated cellulose/collagen dressing, while 758 received control. Using dichotomous or contentious methods and a random or fixed‐effect model, odds ratios (OR) and mean difference (MD) with 95% confidence intervals (CIs) were estimated to evaluate the impact of oxidised regenerated cellulose/collagen dressing on the management of chronic skin wounds. The oxidised regenerated cellulose/collagen dressing had significantly higher complete wound healing (OR, 1.74; 95% CI, 1.06–2.85; P = .03), higher wound relative reduction percent (MD, 13.50; 95% CI, 2.39–24.61; P = .02), and lower adverse events in wound healing (OR, 0.63; 95% CI, 0.41–0.98; P = .04) compared with control in chronic skin wounds. The oxidised regenerated cellulose/collagen dressing had significantly higher complete wound healing, higher wound relative reduction percent and lower adverse events in wound healing compared with control in chronic skin wounds. The low sample size of 8 out of 10 researches in the meta‐analysis and the small number of studies in several comparisons calls for care when analysing the results.